2015
DOI: 10.1007/s00265-015-1897-x
|View full text |Cite
|
Sign up to set email alerts
|

Does lactation lead to resource allocation trade-offs in the spotted hyaena?

Abstract: Life history theory predicts that when food intake and body reserves are insufficient to maintain all life processes, resource allocation trade-offs should occur. Lactation is costly and requires increased food intake. In spotted hyaenas, energy expenditure on lactation is high, particularly for mothers rearing twin litters, and foraging effort and food intake are influenced by social status. We investigated whether lactation in this species results in a reduction in resource allocation to immune processes suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 76 publications
(99 reference statements)
5
51
1
Order By: Relevance
“…Our analyses revealed that changes in FEC across the season were influenced by reproductive effort: females that reproduced (Figure , Supporting Information Table S1) and those that produced heavier litters (Figure b, Supporting Information Table S2) exhibited steeper rises in FEC across the season. These observations mirror the reproduction‐induced increase in parasite burden exhibited in many studies previously, including in Soays (Leivesley et al, ), bighorn sheep Ovis canadensis (Festa‐Bianchet, ), domestic sheep (Beasley et al, ) and other wild vertebrates (East et al, ; Knowles et al, ; Nordling et al, ). These results could potentially be attributed to two mechanisms: a cost of reproduction, in the form of fewer resources remaining for allocation to immune‐mediated parasite resistance (Sheldon & Verhulst, ), or an increase in exposure across the season as hungry females spend more time foraging in nutrient‐rich, but also parasite‐rich tussock vegetation (Hutchings, Milner, Gordon, Kyriazakis, & Jackson, ).…”
Section: Discussionsupporting
confidence: 80%
“…Our analyses revealed that changes in FEC across the season were influenced by reproductive effort: females that reproduced (Figure , Supporting Information Table S1) and those that produced heavier litters (Figure b, Supporting Information Table S2) exhibited steeper rises in FEC across the season. These observations mirror the reproduction‐induced increase in parasite burden exhibited in many studies previously, including in Soays (Leivesley et al, ), bighorn sheep Ovis canadensis (Festa‐Bianchet, ), domestic sheep (Beasley et al, ) and other wild vertebrates (East et al, ; Knowles et al, ; Nordling et al, ). These results could potentially be attributed to two mechanisms: a cost of reproduction, in the form of fewer resources remaining for allocation to immune‐mediated parasite resistance (Sheldon & Verhulst, ), or an increase in exposure across the season as hungry females spend more time foraging in nutrient‐rich, but also parasite‐rich tussock vegetation (Hutchings, Milner, Gordon, Kyriazakis, & Jackson, ).…”
Section: Discussionsupporting
confidence: 80%
“…We continuously monitored three hyena clans located at the centre of the Serengeti NP (East et al., ; Hofer & East, ) between 1990 and 2010. Data were collected from all clan members and individuals were identified by their unique spot patterns, scars and other characteristics such as ear notches.…”
Section: Methodsmentioning
confidence: 99%
“…There may be substantial variation among members of a group in their degree of exposure to a given pathogen and in the outcome of infection (Beldomenico & Begon, ; VanderWaal & Ezenwa, ). Body condition and the ability to allocate resources to immune processes can profoundly affect the outcome of infection as can sex, age and social status (East et al., ; Schmid‐Hempel, ). Quantifying individual differences in the outcome of infection and determining the impact of infection on Darwinian fitness in wildlife populations may be a challenge because diagnosing the infection status for large numbers of individuals is difficult in practice, particularly if only non‐invasive methods are available (Gimenez, Lebreton, Gaillard, Choquet, & Pradel, ; McClintock et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also compared these results with those generated by the classical coprological method of parasite egg or oocyst counts as applied, for instance, by East et al (2015) to assess whether the results of these methods were strongly correlated.…”
Section: Introductionmentioning
confidence: 99%